f(x) = x^3 + x^2 - 42x

factor x out and equate to zero

x(x^2+x-42)=0

x=0

x^2+x-42=0

x^2+7x-6x-42=0

x(x+7)-6(x+7)=0

(x+7)(x-6)=0

x=-7 0r 6 or 0

Hae sharon

Hello my name is Shalon

I remember you do you remember me if you have physics question or maths I can assist you

Give me good rating

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up